Application and outcomes of extracorporeal life support in emergency general surgery and trauma. (September 2022) - Brewer, Jennifer M; Tran, Anthony; Yu, Jielin; Ali, M Irfan; Poulos, C M; Gates, Jonathan; Underhill, David; Gluck, Jason
Background: We analyzed the use of Extracorporeal Membranous Oxygenation (ECMO) in acute care surgery patients at our Level-1 trauma center. We hypothesized that this patient population has improved ECMO outcomes. Methods: This was a retrospective analysis of emergency general surgery and trauma patients placed on ECMO between the periods of October 2013 and February 2020. There were 10 surgical and 12 trauma patients studied, who eventually required ECMO support. ECMO support and ECMO type/modality were analyzed with injury and survival prognostic scores examined. Main results: Overall, 16 of the 22 patients survived to hospital discharge, for a survival rate of 73%. Mean age was 34.18 years. Mean hospital length of stay was 23.4 days with mean days on ECMO equal to 7.5. The net negative fluid balance was 5.36 L. Conclusions: The survival of our ECMO cohort is notably higher than previously cited studies. Our group demonstrated decreased length of time on ECMO, decreased length of stay in the hospital, and similar rates of complications compared to prior reports. ECMO is a useful modality in acute care surgical patients and should be considered in these patient populations. Our focus on net negative fluid balance for ECMO patients demonstrates improved survival. ECMO should be considered early in surgical patients and early in advanced trauma life support.